Effects of military expenditure on economic growth and investment in selected countries - Mohd Tahir, Hirnissa (2012)
The objective of this study is investigate the relationship between military expenditure,economic growth and investment in a global perspective covering 86 selected countries,which comprises OECD and developing countries for the period 1989 to 2006. The main objective in this study is to determine the impact of military expenditure on economic growth as well as the impact of economic growth on military expenditure, while the second objective is to determine the factors affecting the demand for military expenditure, and the third objective is to determine the impacts of military expenditure on investment. To achieve these objectives, we employed the Generalized Method of Moment (GMM) estimator popularized by Arellano and Bond (1991), and Blundell and Bond (1998). For this purpose, we used macroeconomic and institutional variables such as population, openness, trade balance, government expenditure, gross domestic product per capita, foreign direct investment, lending rate, polity, international warfare and regional societal as explanatory variable. Our result suggests that military expenditure has negative impact on growth, while economic growth has positive impact on military expenditure. Our result also suggests that income level, openness, trade balance, polity and regional and civil disturbance are important determinants for military expenditure. Finally our results further suggest that military expenditure, foreign direct investment, lending rate, openness and regional disturbance are important determinants for investment expenditure. As conclusions this study indicate that spending on military is unproductive venture because do not contribute to economic growth, while income does has an impact on the level of military expenditure. Lessons that could be learned by policy makers is that they could cautiously plan the national budget in order not to overspend on military expenditure and depriving other productive sectors such as education and health.